2022
DOI: 10.1109/access.2022.3166632
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Local Path Planning Algorithm Based on Predictive Artificial Potential Field

Abstract: Energy efficiency is one of the most important parameters in transportation electrification. It allows to improve the production rate due to longer operation without charging or decrease the cost related to transportation. To provide collision-free operation in unknown or various environment, the local path planning algorithm should be considered. An Artificial Potential Field (APF) algorithm is commonly used for this task, however it provides unsmooth and oscillating motion of autonomous ground vehicle (AGV),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…They added the robot's energy consumption model to DWA's cost function and achieved different percentages of the reduction in the energy consumption by changing the constant gains. In more recent work on this topic, Szczepanski et al [30] suggested an energy-efficient local path planning based on predictive Artificial Potential Field (APF). Also, their method could reduce the energy consumption of a small robot.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…They added the robot's energy consumption model to DWA's cost function and achieved different percentages of the reduction in the energy consumption by changing the constant gains. In more recent work on this topic, Szczepanski et al [30] suggested an energy-efficient local path planning based on predictive Artificial Potential Field (APF). Also, their method could reduce the energy consumption of a small robot.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…,n s 0.1i l 0. j (10) where s ci and l cj are the coordinates of the sampling point, l tlim and l ulim are the topmost and bottom of the region, s tlim and s ulim are the leftmost and rightmost of the region, respectively, and s tlim and s ulim can be calculated by the following equation:…”
Section: A Generate Sampling Pointsmentioning
confidence: 99%
“…The artificial potential field algorithm is a prevalent technique in robot navigation and path planning [8]. Drawing inspiration from the concept of potential fields in physics, this algorithm models the path of a robot or a moving entity by simulating particle motion within a potential field [10]. At its core, this approach guides the robot along a feasible path by creating a potential field that attracts the target to the robot while repelling the robot from obstacles [11].…”
mentioning
confidence: 99%
“…When the MIB receives ξ rise , it will autonomously recognise the CoG of the user by WDPDM and send the coordinate ( X user , Y user ) to the TR. The path planning of the TR is based on the artificial potential field algorithm [23]. The influence of target position and obstacles on robot motion is concretised into an artificial momentum field, and the combined force controls the robot to move towards the target point along the negative gradient direction of the potential field. Identify the dynamic position and attitude of the legs. …”
Section: Bed Fall Risk Detection and Assisted Getting‐up‐transfermentioning
confidence: 99%